Untraceable blind signature schemes based on discrete logarithm problem - Lee, CC; Yang, WP; Hwang, MS (My University, 2003)
With the help of a blind signature scheme, a requester can obtain a signature on a message from a signer such that the signer knows nothing about the content of the messages and is unable to link the resulting message-signature pair; namely, a blind signature scheme can achieve both blindness and untraceability. Due to the above properties, the blind signature scheme can be used in cryptographic applications such as electronic voting systems and cash payment systems. So far, most of the proposed blind signature schemes are based on the difficulty of solving the factoring problem and quadratic residues. In this paper, the authors intend to propose two new untraceable blind signature schemes based on the difficulty of solving the discrete logarithm problem. The two blind signature schemes are two variations of the DSA signature scheme and can fully satisfy all of the properties a blind signature scheme can have.
Keywords: blind signature; cryptography; DSA; RSA